Restorative Justice and Environmental Crime: Exploring New Models for Addressing Harm to the Environment and Communities - Indah Fhadilah; Livvy Asyafira; Asmak Ul Hosnah (Enigma in Law, 2025)
Environmental crime poses a significant threat to ecological health and community well-being. Traditional punitive approaches often fail to address the root causes of environmental harm and may neglect the needs of affected communities. This study explored the potential of restorative justice as an alternative framework for addressing environmental crime, focusing on its capacity to repair harm, foster accountability, and promote community participation in environmental protection. This research employed a qualitative documentary analysis approach. Relevant documents were analyzed, including legal frameworks and policy documents related to environmental crime and restorative justice, case studies and reports on restorative justice initiatives in environmental contexts, and media reports and online resources. Data were coded and thematically analyzed to identify key themes and patterns related to the application of restorative justice in environmental crime cases. The analysis revealed several key themes: (1) the diverse forms of harm caused by environmental crime, extending beyond ecological damage to include social, economic, and cultural impacts on communities; (2) the limitations of traditional legal responses in addressing the complex nature of environmental harm and providing redress to affected communities; (3) the potential of restorative justice to facilitate dialogue, foster accountability, and develop creative solutions that address the needs of victims, offenders, and the environment; (4) the emergence of innovative restorative justice models in environmental contexts, such as environmental mediation, community conferences, and ecological restoration projects. In conclusion, restorative justice offers a promising framework for addressing environmental crime by promoting healing, accountability, and community engagement. Further research is needed to evaluate the long-term effectiveness of restorative justice initiatives in environmental contexts and to develop best practices for their implementation.